2023
DOI: 10.3389/fonc.2023.1104425
|View full text |Cite
|
Sign up to set email alerts
|

A novel inflammation-related prognostic model for predicting the overall survival of primary central nervous system lymphoma: A real-world data analysis

Abstract: BackgroundPrimary central nervous system lymphoma (PCNSL) is a type of extranodal non-Hodgkin lymphoma. Although there are widely used prognostic scores, their accuracy and practicality are insufficient. Thus, a novel prognostic prediction model was developed for risk stratification of PCNSL patients in our research.MethodsWe retrospectively collected 122 patients with PCNSL from two medical centers in China from January 2010 to June 2022. Among them, 72 patients were used as the development cohort to construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The involvement of inflammation in tumor progression has recently become a focal point of oncology research, as inflammation is involved in tumor growth, including shaping the microenvironment and promoting cancer cell proliferation, survival, and migration [ 18 ]. Many inflammatory parameters correlate with lymphoma prognosis, including the NLR [ 14 ], dNLR [ 19 ], lymphocyte-to-monocyte ratio [ 20 ], and SIRI [ 21 ]; however, none of these was significant associated with survival outcomes in this study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The involvement of inflammation in tumor progression has recently become a focal point of oncology research, as inflammation is involved in tumor growth, including shaping the microenvironment and promoting cancer cell proliferation, survival, and migration [ 18 ]. Many inflammatory parameters correlate with lymphoma prognosis, including the NLR [ 14 ], dNLR [ 19 ], lymphocyte-to-monocyte ratio [ 20 ], and SIRI [ 21 ]; however, none of these was significant associated with survival outcomes in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Tejpal et al [ 34 ] found that the mean PNI significantly differed between patients with PCNSL ( n = 42) and high-grade glioma ( n = 16). A retrospective PCNSL study reported an association between the PNI and OS in the univariate analysis ( p = 0.004) but not the multivariate analysis [ 21 ]. Wong et al [ 29 ] found that the PNI impact both OS and PFS in a retrospective experiment of 41 PCNSL patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CSF B2M levels hold promise as an adjunctive diagnostic indicator for CNS lymphoma (Inoue et al 2023 ). Besides, in both univariate and multivariate Cox analyses, plasma B2M levels in CNS lymphoma patients was also found to be associated with prognosis (Wu et al 2023 ). These findings suggest that B2M levels in plasma might serve as an indicator for distinguishing CNS lymphoma from other types of intracranial tumors and non-CNS lymphoma, and predicting patient outcomes in CNS lymphoma.…”
Section: Role Of B2m In Specific Cns Diseasesmentioning
confidence: 99%